2021
DOI: 10.3389/fnut.2021.652984
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Inhibits Enzymatic Browning of Fresh-Cut Chinese Water Chestnuts

Abstract: This work investigates the role of hydrogen sulfide (H2S) in the browning and regulating the antioxidant defensive system in fresh-cut Chinese water chestnuts. The samples were fumigated with 0, 10, and 15 μl L−1 of H2S and stored at 10°C for 8 days. The results indicated that the H2S treatment significantly inhibited the browning of fresh-cut Chinese water chestnuts, reduced superoxide anion (O2·-) production rate and H2O2 content accumulation, promoted the increase of total phenol content, and enhanced activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 58 publications
4
23
0
Order By: Relevance
“…For example, ascorbic acid, a commonly used anti-browning reagent, couldn’t inhibit browning in FWC ( Song et al, 2019b ). Other chemical compounds, such as hydrogen sulfide (with a concentration of 15 μL L -1 ), could only inhibit around 40 % browning in FWC ( Dou et al, 2021 ). Compared to other known techniques, EUG exhibited a better effect on inhibiting tissue browning in FWC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, ascorbic acid, a commonly used anti-browning reagent, couldn’t inhibit browning in FWC ( Song et al, 2019b ). Other chemical compounds, such as hydrogen sulfide (with a concentration of 15 μL L -1 ), could only inhibit around 40 % browning in FWC ( Dou et al, 2021 ). Compared to other known techniques, EUG exhibited a better effect on inhibiting tissue browning in FWC.…”
Section: Resultsmentioning
confidence: 99%
“…The assay mixture (3 mL) contained 2.45 mL of PBS (0.05 mol L -1 , pH 7.0), 0.5 mL H 2 O 2 (15 mmol L -1 ) and 0.05 mL extract. One unit of CAT activity was calculated as the amount of enzyme that caused a change in absorbance at 240 nm of 0.01 per min ( Dou et al, 2021 ). For each experiment, 18 individual FWC were used to measure CAT activity with three replicates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the ERF2 - bHLH2 - CML5 module may be not only involved in the regulation of calcium signaling, but also in the regulation of H 2 S production in postharvest calcium-deficient apples. It was reported that H 2 S could reduce ROS production and increase antioxidant capacity, thereby extending postharvest life of banana [ 42 ] and inhibiting enzymatic browning of fresh-cut Chinese water chestnuts [ 43 ]. Meanwhile, in Arabidopsis thaliana roots, H 2 S induces ROS accumulation, thus inducing the appearance of Ca 2+ signal [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%